Integration of Prophetic Leadership in The Islamic Education Curriculum for The Formation of Elementary School Students’ Character - Tafriji, Ilham; Amirudin, Amirudin; Arifudin, Yadi Fahmi (Jurnal Cendekia Media Komunikasi Penelitian dan Pengembangan Pendidikan Islam, 2026)
This study aims to analyze in depth how the prophetic leadership values of amanah (trustworthiness), fathanah (wisdom), siddiq (truthfulness), and tabligh (communication) are integrated into the Islamic Religious Education curriculum and their implications for the moral development of Islamic elementary school students. This study uses a qualitative approach, with field research conducted in Islamic elementary schools, and research subjects include Islamic Religious Education teachers, principals, and curriculum coordinators. Data were collected through in-depth interviews, learning observations, and curriculum document analysis, then analyzed using source and method triangulation techniques to ensure data validity. The results show that the integration of prophetic leadership into the PAI curriculum is carried out systematically through three key aspects, namely curriculum planning that includes prophetic value indicators, teaching and learning based on teacher role modelling and active student participation, and character evaluation that emphasizes behavioral change and spiritual reflection. Empirical findings show significant improvements in students’ responsibility, honesty, empathy, and leadership skills in their daily school life. Theoretically, this study enriches the development of a prophetic leadership-based Islamic Religious Education curriculum model in the context of contemporary Islamic education. In practice, the research results provide an implementable reference for Islamic schools in designing a curriculum that is not only cognitively oriented but also effective in shaping students’ morals and leadership character from the elementary level.